Effect of dexmedetomidine on the Montreal Cognitive Assessment in older patients undergoing pulmonary surgery. Issue 9 (September 2022) - Liu, Tao; Liu, Fang-Chao; Xia, Yu; Luo, Tai-Jun; Wang, Fei; Chen, Bin; Wang, Chun; Gao, Guang-Kuo; Zhai, Wen-Ting; Liu, Wei
Objective: We investigated the effect of dexmedetomidine anesthesia on postoperative cognitive function after pulmonary surgery. Methods: A blinded, prospective, randomized, placebo-controlled study was performed on 60 patients (age range 65–74 years) undergoing lobectomy by video-assisted thoracoscopic surgery (29 in the dexmedetomidine group; 31 in the placebo group). Dexmedetomidine group patients received dexmedetomidine, and placebo group patients received an equal volume of physiological saline 20 minutes before anesthesia induction. Cognitive function was evaluated using the Montreal Cognitive Assessment 1 day before surgery and on postoperative day (POD)1, POD3, and POD7. The regional cerebral oxygen saturation (rSO2 ) was monitored continuously by near-infrared spectroscopy before anesthesia. Results: The Montreal Cognitive Assessment score was significantly different between the two groups on POD1 (dexmedetomidine 26.4  ±  0.73 vs . placebo 25.5 ± 0.96) and POD3 (dexmedetomidine 27.1 ± 0.79 vs . placebo 26.6 ± 0.80). Specifically, attention and orientation scores were increased in the dexmedetomidine group on POD1 and POD3. The rSO2 was not significantly different between the dexmedetomidine and placebo groups. Conclusion: Dexmedetomidine given before induction of anesthesia could reduce the risk of postoperative cognitive dysfunction and might not decrease rSO2 . Hence, dexmedetomidine could be employed in pulmonary surgical procedures, especially for older patients with a high risk of cognitive dysfunction.